(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2022)
Herbal preparation like herbal tablets, herbal tonics, herbal paste, herbal shampoo, herbal contraceptives, herbal dyes has become popular among the consumer herbal medicines represent the fastest growing segment to heal the various ailments. The main aim and object of present study is formulation and evaluation of herbal hair dye, investigating the alternative to the synthetic and semisynthetic dyes. Loss of color in hair is due to varied reasons like genetic influence, effect of environment factors, reasons like use of alcoholic preparations etc. Herbs are widely used as remedial agents because such drugs are easily available at low cost and comparatively safe and the people have good faith in such remedies. In India , ayurvedic system evolved over 5000 years and ago and is still in practice. Herbal formulations have growing demand in the world market. To overcome this entire problem was the main intention of our project. So we prepared hair dye powder which is multipurpose powder for hair dyeing treatment. The current research was aimed at the preparation of herbal hair dye and the evaluation of its various parameters as organoleptic, physio chemical, phytoconstituents, rheological aspects, patch test and stability testing for its efficacy and shelf life.